1991
DOI: 10.1128/jb.173.9.2809-2817.1991
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of a region of the Rhizobium meliloti pSym plasmid specifying catabolism of trigonelline, a secondary metabolite present in legumes

Abstract: Genes controlling the catabolism of trigonelline, a secondary metabolite that is often present in legumes, are located on the pSym megaplasmid of Rhizobium meliloti. To investigate the role of bacterial trigonelline catabolism in the Rhizobium-legume symbiosis, we identified and characterized the R. meliloti RCR2011 genetic loci (trc) controlling trigoneline catabolism. Tn5-B20 mutagenesis showed that the trc region is a continuous DNA segment of 9 kb located 4 kb downstream of the nifAB and fdxN genes. Trc mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…The noncatabolizable betaines DMSP and HB did not support growth of the metH strain in LAS medium (data not shown). Similarly, another betaine, trigonelline, was not used as a methionine precursor by the metH strain; this observation is consistent with the fact that trigonelline is catabolized in S. meliloti by a BHMT-independent pathway (4,5). Taken together, these results are consistent with the hypothesis that BHMT is the only S. meliloti enzyme that allows methionine production from betaines.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The noncatabolizable betaines DMSP and HB did not support growth of the metH strain in LAS medium (data not shown). Similarly, another betaine, trigonelline, was not used as a methionine precursor by the metH strain; this observation is consistent with the fact that trigonelline is catabolized in S. meliloti by a BHMT-independent pathway (4,5). Taken together, these results are consistent with the hypothesis that BHMT is the only S. meliloti enzyme that allows methionine production from betaines.…”
Section: Resultssupporting
confidence: 80%
“…Glycine betaine is transiently accumulated (43), and dimethylsulfonioacetate (DMSA) is catabolized only in medium of low osmolarity (32). Some betaines, like trigonelline, have been shown to be involved in the nodulation process and are catabolized through a specific pathway (4).…”
mentioning
confidence: 99%
“…For example, genes involved in the synthesis of melanin (3,9) and bacteriocins (28) are found on symbiotic plasmids. In Rhizobium meliloti, Boivin et al (4) identified genes involved in the catabolism of trigonelline, a secondary metabolite secreted by some legumes. Similarly, Murphy et al (36) have identified R. meliloti genes that synthesize opinelike compounds in nodules; these compounds are thought to be secreted and stimulate rhizosphere growth of strains of R. meliloti that have the capacity to utilize the opinelike metabolite.…”
mentioning
confidence: 99%
“…Trigonelline (8,10) and L-homoserine (21) catabolic genes are located on the Symbiotic (Sym) plasmid, which carries genes involved in nitrogen fixation (nif) and nodulation (nod), whereas calystegin catabolic genes in Rhizobium meliloti 41 are encoded on the cryptic plasmid pRme4la (59). The Sym plasmid location of catabolic genes points towards a symbiotic role for these compounds.…”
mentioning
confidence: 99%